2017
DOI: 10.1111/jsbm.12363
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Role of National Culture in the Relationship Between University Entrepreneurship Offerings and Student Start-Up Activity: An Embeddedness Perspective

Abstract: Student proclivity to start a venture can be affected not only by the university environment where they are exposed to entrepreneurship, but also by perceptions of how desirable entrepreneurial behavior is considered to be in a given society. Based on an embeddedness perspective, and using a sample of students from 26 countries and 489 universities, evidence is produced of significant positive relationships between both curricular and co-curricular programing and student start-up activities, with specific cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(91 citation statements)
references
References 137 publications
3
74
0
7
Order By: Relevance
“…Concerning the gender gap debate, our results were consistent with previews scholars' findings, which concluded that business is still perceived as a male issue in the footprint (Dawson & Henley, 2015;Johansen, 2013;Minniti & Naudé, 2010). Furthermore, gaps are shown at the least in entrepreneurship education and entrepreneurial intention relation, supporting that females are less oriented towards entrepreneurship compared to males (Cañizares & García, 2010;Goktan & Gupta, 2015;Joensuu-Salo, Varamäki, & Viljamaa, 2015;Maes, Leroy, & Sels, 2014;Maresch, Harms, Kailer, & Wimmer-Wurm, 2016;Perez-Quintana, Hormiga, Martori, & Madariaga, 2017;Shirokova, Tsukanova, & Morris, 2018). Similar results were found even in other European countries (i.e.…”
Section: Empirical Results and Discussionsupporting
confidence: 91%
“…Concerning the gender gap debate, our results were consistent with previews scholars' findings, which concluded that business is still perceived as a male issue in the footprint (Dawson & Henley, 2015;Johansen, 2013;Minniti & Naudé, 2010). Furthermore, gaps are shown at the least in entrepreneurship education and entrepreneurial intention relation, supporting that females are less oriented towards entrepreneurship compared to males (Cañizares & García, 2010;Goktan & Gupta, 2015;Joensuu-Salo, Varamäki, & Viljamaa, 2015;Maes, Leroy, & Sels, 2014;Maresch, Harms, Kailer, & Wimmer-Wurm, 2016;Perez-Quintana, Hormiga, Martori, & Madariaga, 2017;Shirokova, Tsukanova, & Morris, 2018). Similar results were found even in other European countries (i.e.…”
Section: Empirical Results and Discussionsupporting
confidence: 91%
“…(см., напр. : [McGrath, MacMillan, Scheinberg, 1992;Mueller, Thomas, 2001;Shane, 1992;1993;Thomas, Mueller, 2000;Marino et al, 2002;Stewart et al, 2003]) и также продолжают применять в настоящее время [Li, Zahra, 2012;Dheer, 2017;Watson et al, 2017;Shirokova, Tsukanova, Morris, 2018]. Одна-ко в связи с постепенным устареванием оценок соответствующих параметров на-циональной культуры и разнонаправлен-ной критикой теории Г. Хофстеде (см., напр.…”
Section: результаты анализаunclassified
“…Третье направление исследований связи национальной культуры и предпринима-тельства рассматривает роль культуры в формировании индивидуальной предпри-нимательской активности De Clercq, Lim, Oh, 2013;Stephan, Pathak, 2016;Shirokova, Tsukanova, Morris, 2018] и предпринимательских намерений [Liñán, Chen, 2009;Shinnar, Giacomin, Janssen, 2012;Shneor, Camgöz, Karapinar, 2013;Giacomin, Janssen, Shinnar, 2016]. Особое внимание уделяется также изуче-нию личностных характеристик, присущих предпринимателю [McGrath, MacMillan, Scheinberg, 1992;Mueller, Thomas, 2001;Thomas, Mueller, 2000;Stewart et al, 2003]; предпринимательского познания [Mitchell et al, 2000;Mitchell et al, 2002]; отношения к предпринимательству [Drakopoulou Dodd, Jack, Anderson, 2013] и же-лательности и возможности предприни-мательского поведения [Minola, Criaco, Obschonka, 2016], поскольку они способны оказать воздействие на поведение индиви-да и его намерения открыть собственный бизнес.…”
Section: направления исследований связи национальной культуры и предпunclassified
See 1 more Smart Citation
“…University entrepreneurship programmes and strategies have always been one of the most successful ways how to prepare future entrepreneurs and business managers (Shirokova et al 2018). Innovations that address the world's biggest problems require an understanding of human relationships, an appreciation of interpersonal relationships that brings different perspectives to the table, and a relentless pursuit of collaboration (Porter and Kramer 2006).…”
Section: Introductionmentioning
confidence: 99%